2017
DOI: 10.1007/s10826-017-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Levels in Children with Autism Spectrum Disorder: A Meta-Analysis

Abstract: The aim of the current study was to meta-analytically examine whether anxiety levels in children with autism spectrum disorders (ASD) are elevated. A total of 83 articles were selected from a systematic literature search and were included in the meta-analyses. Results demonstrated that children with ASD had higher anxiety levels compared to typically developing children, and this difference increased with IQ. Youth with ASD also tended to have higher anxiety levels compared to clinically referred children, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
132
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 105 publications
10
132
2
3
Order By: Relevance
“…Results from the open field test revealed that (COX)‐2 − mice have elevated ambulatory activity and adult (COX)‐2 − males spend less time in the center, which are analogous to greater hyperactivity and anxiety behaviors, respectively . These behaviors seem to be comparable with symptoms commonly reported in ASD cases . For example, a number of cross‐sectional studies have reported that 40% to 55% of children with ASD also had ADHD or anxiety disorders .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Results from the open field test revealed that (COX)‐2 − mice have elevated ambulatory activity and adult (COX)‐2 − males spend less time in the center, which are analogous to greater hyperactivity and anxiety behaviors, respectively . These behaviors seem to be comparable with symptoms commonly reported in ASD cases . For example, a number of cross‐sectional studies have reported that 40% to 55% of children with ASD also had ADHD or anxiety disorders .…”
Section: Discussionsupporting
confidence: 76%
“…The marble burying test showed that (COX)‐2 − animals buried a higher number of marbles compared with WT controls representing increased repetitive and anxiety‐related behaviors, which are characteristic symptoms of autism . Sex differences were also seen in control and (COX)‐2 − animals: males buried more marbles than females suggesting that males show higher levels of anxiety‐related and repetitive behaviors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Anxiety is typically viewed as a negative condition associated with higher levels of stress and mental health disorders (Mash and Barkley, 2003). However, some research indicates that increased anxiety is associated with better functioning in social/communication domains in children with ASD (Van Steensel and Heeman, 2017). Future research could therefore dissect the complex relationship between anxiety and nature in youth with ASD in more detail, perhaps using in-depth clinical anxiety measures with sub-scales for social and non-social anxiety facets as well as language/communication outcome variables (Grills and Ollendick, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that adolescents with ASDs are at greatly increased risk of depression and anxiety disorders (Hofvander et al, ; Lugnegard, Hallerback, & Gillberg, ). The discrepancy between prevalence rates of depression and anxiety in ASD compared to TD populations increases with age during adolescence (van Steensel & Heeman, ), indicating specific vulnerability in adolescents with ASDs. Rates of suicidality are higher in the ASD than in the TD population—a difference that also emerges during late adolescence and the transition to young adulthood (Veenstra‐Vander Weele, ).…”
mentioning
confidence: 99%